PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PENALARAN MATEMATIKA SISWA DI KELAS VII SMP YAYASAN PENDIDIKAN ISLAM DELI TUA TA. 2016/2017 - siti aminah nasutuion (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This study aims to find out (1) The ability of students' mathematical reasoning that is taught by realistic mathematics approach (2) The ability of students' mathematical reasoning that is taught by conventional learning (3) Is there a comparison of the effect of realistic mathematical approach and conventional learning to students' VII Junior Islamic Education Foundation Deli Tua T.A 2016/2017. This research is quantitative research. The population of this research is all students of class VII SMP Islamic Education FoundationDeli Tua consisting of 151 students. The sample in this research is class VII-4 amounted to 26 students as experimental class and class VII-5 amounted to 25 students as control class. The findings of this research show: (1) The students 'math competence ability which is taught by realistic mathematical approach get the average score of 67,30 (2) The students' math competency which is taught by conventional learning gets the average score of 59,29 (3 ) There is a comparison of the effect of realistic mathematical approach and conventional learning on the mathematical reasoning ability of the seventh grade students of SMP Yayasan Pendidikan Islam Deli Tua T.A 2016/2017. This is based on the calculation of statistical test-t obtained by the number of 1.792 while the t-table of 1.676. Thus, there is a comparison of the effect of realistic mathematical approach and conventional learning on students' math reasoning ability.